2019
DOI: 10.1002/crq.21271
|View full text |Cite
|
Sign up to set email alerts
|

Reflective structured dialogue: A qualitative thematic analysis

Abstract: Reflective Structured Dialogue (RSD) is a specific type of dialogue intervention designed to help individuals on opposing sides of controversial political and social issues share their perspectives, and communicate in a manner that allows them to better understand one another. The current study examined outcomes from case studies on RSD using qualitative thematic analysis. Eight articles were analyzed, using an inductive grounded theory approach. The major themes that emerged were embracing multiple perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…Together, the quantitative data and participant comments suggest that, as in previous studies, RSD helped participants create connections and understand different perspectives ( 15 , 21 ). This study also helps demonstrate how deliberative inquiry can contribute to student learning in higher education setting ( 12 ).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Together, the quantitative data and participant comments suggest that, as in previous studies, RSD helped participants create connections and understand different perspectives ( 15 , 21 ). This study also helps demonstrate how deliberative inquiry can contribute to student learning in higher education setting ( 12 ).…”
Section: Discussionsupporting
confidence: 62%
“…While extensive research has documented the positive effects of various types of dialogue on polarization and conflict reduction, rigorous studies specific to RSD are more limited; however, the existing evidence related to RSD is promising. For example, a qualitative study showed that RSD can create and deepen positive connections, increase self-reflection and growth, improve communication skills, and help people understand different perspectives and viewpoints ( 15 ). Another case study found that RSD helped build trust and strengthen relationships between people that had opposing viewpoints on LGBTQ+ inclusion in a university setting ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main focus of RSD is on promoting a space for speaking and listening among everyone, rather than aiming to reach consensus. Among the results obtained using this approach are: interest in more dialogue meetings; change in the way of dialoguing with antagonistic groups; inspiration for possible joint actions (Souza et al, 2019); greater receptivity to different opinions; greater freedom and empowerment to address conflicting issues; the ability to accept multiple realities; more positive and stronger connections between people; higher levels of empathy; the recognition of common points between opposing groups; and greater potential for collaborative relationships (Gower et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Students and staff from different racial groups should take an early opportunity to integrate in meaningful ways, such as through developing reciprocal relationships. One method could be through medical schools creating reflective structured dialogue groups (SDGs) 8 and incorporating them as mandatory parts of medical students' training and faculty members' professional development. SDGs involve individuals formally coming together, divulging information about themselves, and reflecting on their educational experiences in a non‐judgmental setting.…”
mentioning
confidence: 99%